2005
DOI: 10.1124/jpet.104.080846
|View full text |Cite
|
Sign up to set email alerts
|

JTP-27536 [(+)-1,3-Dihydroxy-2-hydroxymethylpropyl-2-ammonium 2-[(R)-3-Cyclo-hexyl-1-phenylpropyl]-1,3-dioxo-2,3-dihydro-1H-isoindole-5-carboxylate Monohydrate], a Novel Inhibitor of Immunoglobulins and Interleukin-5 with Anti-Inflammatory Properties in Mouse Allergic Dermatitis Model

Abstract: We report a novel synthetic compound JTP-27536 [(ϩ)-1,3-dihydroxy-2-hydroxymethylpropyl-2-ammonium 2-[(R)-3-cyclohexyl-1-phenylpropyl]-1,3-dioxo-2,3-dihydro-1H-isoindole-5-carboxylate monohydrate] as an inhibitor of immunoglobulins (Igs) and interleukin (IL)-5 production in vitro and in vivo. JTP-27536 inhibited IgE production in mouse and human B cells with IC 50 values of 2.5 and 2.1 M, respectively, and the inhibition was stronger than that on IgG1 and IgM production (IC 50 Ͼ 10 M). JTP-27536 also inhibited… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 29 publications
2
5
0
Order By: Relevance
“…Administration of PBE (12.5, 25, and 50 mg/kg) dose‐dependently decreased in levels of IgE (32%, 42%, and 51%, respectively) and IgG 1 (32%, 47%, and 56%, respectively), whereas serum IgG 2a level was not decreased by PBE. Previous study indicated that PD inhibits IgE, IgG 1 , and IgG 2a in mice (Mimura, Shinozaki, Kawasaki, & Iwamura, ). The PD group showed suppressed serum IgE, IgG 1 , and IgG 2a levels compared with the control group (40%, 50%, and 58%, respectively).…”
Section: Resultsmentioning
confidence: 86%
See 1 more Smart Citation
“…Administration of PBE (12.5, 25, and 50 mg/kg) dose‐dependently decreased in levels of IgE (32%, 42%, and 51%, respectively) and IgG 1 (32%, 47%, and 56%, respectively), whereas serum IgG 2a level was not decreased by PBE. Previous study indicated that PD inhibits IgE, IgG 1 , and IgG 2a in mice (Mimura, Shinozaki, Kawasaki, & Iwamura, ). The PD group showed suppressed serum IgE, IgG 1 , and IgG 2a levels compared with the control group (40%, 50%, and 58%, respectively).…”
Section: Resultsmentioning
confidence: 86%
“…In contrast, PD inhibited not only splenic production of Th2 cytokines and serum level of IgG 1 but also splenic production of IFN‐γ and serum level of IgG 2a . The inhibitory effects of PD were also observed in mouse allergic dermatitis model (Mimura et al, ). These results show that PBE on IgG 2a /IgG 1 ratio appeared to be more effective rather than PD.…”
Section: Discussionmentioning
confidence: 84%
“…Prednisolone treatment is known to decrease AHR, eosinophilia in the lung, serum IgE levels, and IL-2 and IL-4 production by ConA-stimulated splenocytes [38, 39]. However, the side effects of corticosteroids may cause problems.…”
Section: Discussionmentioning
confidence: 99%
“…Others have reported ear swelling responses that were as excessive as 1800 μ m (20). Recently, experimental drugs, such as CX‐659S (16,17), JTP‐27536 (21) and olopatidine‐HCl (15,20) were tested in related chronic inflammation models with contact sensitizers that induced excessive ear swellings larger than 150 μ m. Unless specially required, such as in itch models (22), we conclude that the determination of anti‐inflammatory effects of test compounds does not require excessive ear swellings over 150 μ m.…”
Section: Discussionmentioning
confidence: 93%